Decision making at the front end of innovation: the hidden influence of knowledge and decision criteria. (3rd March 2014) - de Oliveira, Maicon Gouvêa; Rozenfeld, Henrique; Phaal, Robert; Probert, David
<x xml:space="preserve">Abstract</x> Decision making at the front end of innovation is critical for the success of companies. This paper presents a method, called decision making based on knowledge (DeBK), which was created to analyze the decision‐making process at the front end. The method evaluates the knowledge of project information and the importance of decision criteria, compiling a measure that indicates whether decisions are founded on available knowledge and what criteria are in fact being considered to delineate them. The potential contribution of DeBK is corroborated through two projects that faced decision‐making issues at the front end of innovation.